2017
DOI: 10.1016/j.ijsu.2017.03.013
|View full text |Cite
|
Sign up to set email alerts
|

How to diagnose an acutely inflamed appendix; a systematic review of the latest evidence

Abstract: Acute appendicitis is the most common condition that presents with an acute abdomen needing emergency surgery. Despite this common presentation, correctly diagnosing appendicitis remains a challenge as clinical signs or positive blood results can be absent in 55% of the patients. The reported proportion of missed diagnoses of appendicitis ranges between 20% and 40%. A delay or mis-diagnosis of appendicitis can result in severe complications such as perforation, abscess formation, sepsis, and intra-abdominal ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
52
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(72 citation statements)
references
References 59 publications
4
52
0
2
Order By: Relevance
“…A significant concern for clinicians in managing paediatric abdominal pain in ED is the possibility of missed or delayed diagnosis of appendicitis reported to be within the range of 20–40% . This can lead to significant morbidity, including perforation, abscess formation, sepsis and intra‐abdominal adhesions . The rate of misdiagnosis or delayed diagnosis is in keeping with our study findings of an AUC of 0.84 (95% CI 0.76–0.91); however, the small sample size of children who were diagnosed with appendicitis may introduce bias and therefore this will need to be clarified in a larger cohort study.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…A significant concern for clinicians in managing paediatric abdominal pain in ED is the possibility of missed or delayed diagnosis of appendicitis reported to be within the range of 20–40% . This can lead to significant morbidity, including perforation, abscess formation, sepsis and intra‐abdominal adhesions . The rate of misdiagnosis or delayed diagnosis is in keeping with our study findings of an AUC of 0.84 (95% CI 0.76–0.91); however, the small sample size of children who were diagnosed with appendicitis may introduce bias and therefore this will need to be clarified in a larger cohort study.…”
Section: Discussionsupporting
confidence: 84%
“…A significant concern for clinicians in managing paediatric abdominal pain in ED is the possibility of missed or delayed diagnosis of appendicitis reported to be within the range of 20–40% . This can lead to significant morbidity, including perforation, abscess formation, sepsis and intra‐abdominal adhesions .…”
Section: Discussionmentioning
confidence: 99%
“…Fever is one of the variables present in most of the RIFP diagnostic scales (Alvarado, RIPASA, and AIR). However, many authors believe that the predictive value of fever for AA is limited [29,30]. Andersson [31], in a study of 496 patients, demonstrated that a temperature > 37.7 °C had a sensitivity and specificity of 70%…”
Section: Discussionmentioning
confidence: 99%
“…Laparoskoskopija, UZ, CT i laboratorijska dijagnostika tehnički su napredovali. 19 Ipak, klinički postavljena dijagnoza akutnog apendicitisa i dalje je nesigurna. Rješenje se pokušava naći uvođenjem numeričkih sustava bodovanja (Alvaradov je najpoznatiji).…”
Section: Raspravaunclassified